Pharmacognostical, Phytochemical and Pharmacological Evaluation of Monocot Grass Kyllinga Triceps Rottb: Evaluation of Hepatoprotective and Antioxidant Activity of Kyllinga triceps Rottb (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of present study was pharmacognostical phytochemical and pharmacological evaluation of monocot grass kyllinga triceps rottb. In the present study hepatotoxicity was induced by using ccl4, silymarin was takan as standard drug. Ethanolic and petroleum ether extracts were prepared for study. It was observed that among all the extracts of kyllinga triceps rottb, the petroleum ether extract significantly decreased (p>0.01) the SGOT, SGPT, ACP, ALP and DB levels.Petroleum ether extract (200 mg/kg) showed highest hеpatoprotеctive activity almost comparable to the silymarin (25 mg/kg) treated group.It can be decided that the plant kyllinga triceps has revealedsubstantial hеpatoprotеctive action when related to silymarin. In present study complete morphological and microscopical studies were performed with isolation and identification of chemical constituents of the plant, rhizome extract was evaluated for pharmacological afficacy, plant is found effective as hеpatoprotеctive anti-oxidant and diuretic.